Nandi shrine at Jagannath Mahadev Temple - Ghosh, Ayan (2023)
Jagannath Mahadev Temple features a turtle in front of Nandi, both facing the garbagriha. Various theories explain this arrangement seen at all Shiva temples at Walkeshwar. It is believed because a turtle can retract within its shell, it symbolizes withdrawal from the material world (moh-maya) and entering a state of samadhi (meditative consciousness).